Pelatihan Pembuatan Rencana Anggaran Biaya (RAB) Di Kelurahan Pananjung Kecamatan Tarogong Kaler Kabupaten Garut: Training on Making a Budget Plan (RAB) in Pananjung Village, Tarogong Kaler District, Garut Regency - Irma Rosmayati (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
This service activity aims to meet the knowledge needs of the staff of the Government of Pananjung Village, Tarogong Kaler District, Garut Regency and related institutions that take shelter within it. The teaching material provided is in the form of Training on Making a Budget Plan (RAB). The activity was held in the Pananjung Village Hall using the Learning by Doing method. The outputs produced for the participants are training modules, training programs in the form of Microsoft Excel, material price lists, work wage price lists. The results of the training will provide ease of communication in proposing regional development between residents (applicants) and the Pananjung Kelurahan Government (manager).